Integrated bioinformatics analysis reveals Netrin-1 as a key molecular link between Parkinson’s disease and heart failure - Ni, Zhen; Wang, Gaoge; Li, Yingyan; Chen, Huan; Hou, Hongwei; Hu, Qingyuan (Frontiers in Aging Neuroscience, 2025)
BackgroundParkinson’s disease (PD) patients face a higher risk of developing heart failure (HF). The objective of the study was to investigate the hub genes and potential mechanisms linking Parkinson’s disease (PD) to heart failure (HF) using multiple integrative bioinformatics tools.MethodsIntegrated bioinformatics analyses were performed. One HF dataset (GSE57338) and three PD datasets (GSE7621, GSE20146, GSE49036) were obtained from the GEO database. Weighted gene co-expression network analysis (WGCNA) was used to identify PD-related genes. Differentially expressed genes (DEGs) between PD and normal samples, as well as between HF and normal samples, were identified. The intersection of DEGs, WGCNA-derived PD-related genes, and genes encoding known secretory proteins was analyzed to find PD-associated secretory proteins. Immune cell infiltration in HF was assessed using CIBERSORT. Protein-protein interaction (PPI) network analysis was conducted to identify hub genes. Key findings were experimentally validated in an MPTP-induced PD mouse model through behavioral tests, ELISA, and immunohistochemistry.ResultsAnalysis identified 21 PD-associated secretory proteins. Intersection with HF DEGs revealed 12 common genes, from which 8 functional genes with consistent expression patterns in both conditions were identified. PPI network analysis highlighted three hub genes: RELN, SLIT1, and NTN1. Reactome pathway analysis indicated that NTN1 is involved in cardiac-related processes like muscle contraction and cardiac conduction. Experimental validation in PD model mice confirmed a significant decrease in Netrin-1 levels in the blood, striatum, and heart. Furthermore, a strong negative correlation was found between cardiac Netrin-1 expression and collagen deposition, suggesting its potential role in impacting cardiac function.ConclusionThese insights highlight the coexistence of PD and HF and suggest new avenues for investigating strategies to prevent HF in PD patients, particularly by exploring the role of Netrin-1 in the heart and its potential for cardioprotection.